Language-support system using character recognition - Asai, Kikuo; Sugimoto, Yuji Y.; Hemmakorn, Narong; Osawa, Noritaka; Kondo, Kimio (My University, 2004)
We have developed a prototype system that supports language translation for distance lecturing and local learning. The system automatically detects a word displayed in a video image by matching the identified character markers; it then translates the word into the other language and displays the translated word using text, image, and/or sound. The ARToolkit is used as an image-processing tool to search the video image for character markers, which are composed of square .frames and registered characters. The use of image processing enables any language to be used as the source language; Japanese is used in the prototype. The use of video makes it easy to implement the system in existing telecommunication systems, because a user just prepares a PC for capturing video images. A Web browser is used as the presentation tool; it can handle any content format normally supported by a Web browser: images, sounds, 3D models, and characters. An automatic voice function automatically reads out words on user demand. The software consists of a character-recognition part (server) and a display part (client); the server controls the client through socket communications. This software architecture makes it possible for one lecturer to simultaneously teach students with various mother tongues, when the clients treat multi-language, because there is a different client for each student. Testing of this language-support system for distance lecturing between Thailand and Japan using a satellite communication system showed that it could be used for both fundamental language lecturing and language translation during international exchange.
Keywords: ARToolkit; Character recognition; Distance lecture; Language-support; Videoconference